Pertanggungjawaban Notaris atas Cacat Prosedur dalam Akta RUPS Luar Biasa: Kajian Putusan Pengadilan - Yunita, Sahera; Ferdi; Misnar Syam (Universitas Muhammadiyah Yogyakarta, 2025)
Indonesia’s national economy is developed on the foundation of economic democracy and the principle of the rule of law, which ensures certainty, order, and legal protection. Within the corporate sphere, the Limited Liability Company (Perseroan Terbatas/ PT) recognizes the General Meeting of Shareholders (Rapat Umum Pemegang Saham/ RUPS) as its highest organ with strategic authority, where every resolution must be formalized in an authentic deed prepared by a notary. Such deeds serve a crucial role in providing legal certainty and preventing potential disputes. However, practice reveals recurring problems in which RUPS deeds are drawn up without complying with legal procedures, thereby triggering conflicts and causing harm to shareholders. This issue is evident in the Padang District Court Decision No. 10/Pdt.G.S/2023/PN Pdg and the Medan High Court Decision No. 315/Pdt/2021/PT MDN. This study aims to examine the notary’s liability in drafting procedurally defective RUPS deeds and to analyze the legal consequences arising from these judicial decisions. The research employs a normative juridical approach with a descriptive character, combining statutory analysis (statute approach) with conceptual analysis (conceptual approach). The data are derived from primary, secondary, and tertiary legal sources, which are then qualitatively analyzed. The findings demonstrate that notaries in both cases failed to properly observe the principle of prudence, resulting in the deeds being declared invalid or null and void. In the Padang case, the court ordered restitutio in integrum by restoring the plaintiff’s legal position, while in the Medan case, the ruling was limited to annulment of the deed without explicit restitution. These outcomes affirm that notarial responsibility extends beyond formal or administrative duties, encompassing substantive obligations to uphold legal certainty and protect shareholders’ rights.